Climate policy modeling: An online SCI-E and SSCI based literature review. (December 2015) - Wei, Yi-Ming; Mi, Zhi-Fu; Huang, Zhimin
Abstract: This study utilizes the bibliometric method on climate policy modeling based on the online version of SCI-E from 1981 to 2013 and SSCI from 2002 to 2013, and summarizes several important research topics and methodologies in the field. Publications referring to climate policy modeling are assessed with respect to quantities, disciplines, most productive authors and institutes, and citations. Synthetic analysis of keyword frequency reveals six important research topics in climate policy modeling which are summarized and analyzed. The six topics include integrated assessment of climate policies, uncertainty in climate change, equity across time and space, endogeneity of technological change, greenhouse gases abatement mechanism, and enterprise risk in climate policy models. Additionally, twelve types of models employed in climate policy modeling are discussed. The most widely utilized climate policy models are optimization models, computable general equilibrium (CGE) models, and simulation models. Highlights: Bibliometric method is used in climate policy modeling based on the SCI-E and SSCI. Six important research topics in climate policy modeling are analyzed. The IAM is the most popular analysis framework in the climate policy assessment. The most widely utilized models are optimization model, CGE, and simulation model.